THE HISTORY OF THE DEVELOPMENT OF ENGINEERING DRAWING (Educa Journal of Studies, 2026)
The article analyzes the historical and scientific-methodological stages of the development of drafting as a discipline. It examines early graphical representations of ancient civilizations, the formation of scientific foundations during the Renaissance, the standardization of technical drawing during the Industrial Revolution, and the emergence of modern CAD technologies. The importance of drafting in engineering education and professional competence development is substantiated.
Keywords: Drafting, engineering graphics, descriptive geometry, projection, CAD, historical development.